MEMAHAMI PENGALAMAN KOMUNIKASI MAHASISWA ASAL INDONESIA DALAM MENGATASI GEGAR BUDAYA PADA SISTEM PENDIDIKAN DI TAIWAN - Almanda Prinarenti, Aurelia; Rahardjo, Turnomo; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The research was motivated by the culture shock experienced by Indonesian students studying in Taiwan, related to differences in the education system between Taiwan and Indonesia. The selection of Taiwan for research was motivated by the high interest of Indonesian students to continue their education in Taiwan. The research focuses on the education system, including the teaching and learning process in class, group and individual assignments and exams, as well as internships and final projects. The purpose of this research is to understand the communication experiences of Indonesian students in overcoming culture shock in the education system in Taiwan. The research was conducted with an interpretive phenomenological approach and descriptive qualitative research method. The research used Self-Adjustment Theory and Identity Negotiation Theory. The data collection technique was carried out by literature study and in-depth interviews with six students from Indonesia class of 2020, who studied higher education at the undergraduate level in Taiwan. The results found that students need to take the initiative in initiating communication in learning activities and daily life, for example to get acquainted, ask questions, discuss, and get closer, this is because the communication culture in Taiwan tends to be individualistic. Students need to master the use of traditional Mandarin to support the communication process to overcome culture shock, as the main language used by Taiwanese people. Indonesian students need to approach themselves to live in groups in order to communicate and exchange ideas, especially with fellow Indonesian students, but Indonesian students can also avoid communication, in order to take a break from the pressure of educational culture shock, before finally returning to a condition that is ready to communicate.